The verbal episode and the analysis of private verbal behavior (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
In this article, we aim at analyzing the total verbal episode and at describing the controlling variables of thespeaker and listener relationship. Besides, we try to include the possibility of this behavioral process occur ina single person. The concepts of precurrent behavior and chaining are used to show the stimulus control,which is involved, where some class of action produces stimuli that change the probability of subsequentbehavior. So that, we show the possibility that the operant analysis account the solving problem process,where only one or more person act as a speaker and listener, alternatively. Finally, we make the assumptionthat we can ask about instances of private verbal behavior which would be based on public events that aregoing on, and then additional confirming empirical research would be possible.